International Standards Regarding the Working Conditions of Women Workers - Kasturi Kumari,; Professor (Dr.) Vidya Shaktawat, (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This research article focuses on international standards regarding the working conditions of women workers. This includes standards set by the International Labour Organization (ILO) and other global bodies, such as equal pay for equal work, maternity protection, safety at workplace, protection from sexual harassment and social security rights have been studied in detail. The article clarifies that these internationally established standards not only protect the dignity and human rights of women workers but also promote gender equality in the labour sector. It also discusses what practical difficulties and challenges arise in implementing these standards in developing countries, especially in states like India and Bihar. The conclusion of the research paper underlines that effective implementation of international standards is necessary to improve the working conditions of women workers and provide them with dignified labour environment.
Keywords: Women Workers; Working Conditions; International Standards; International Labour Organization; Equal Pay; Maternity Protection; Workplace Safety; Gender Equality; Human Rights Social Protection